COVID-19 and Digital Transformation in Higher Education Institutions: Towards Inclusive and Equitable Access to Quality Education - Molefi Matsieli; Stephen Mutula (MDPI AG, 2024)
While the impact of the COVID-19 pandemic has affected both developing and developed countries, students from disadvantaged groups have suffered significantly. During the pandemic, these students not only struggled to access online education but also faced various forms of exclusion. In the post-COVID-19 pandemic era, this systematic literature review employs the concept of social justice framework to investigate the implications of the COVID-19 pandemic on higher education worldwide, focusing on the opportunities and challenges of digital transformation in ensuring inclusive and equitable access to quality higher education. The findings suggest that while digital transformation in higher education has provided substantive benefits, its adoption has also ushered in challenges for learning. The review emphasizes that higher education institutions (HEIs), alongside their governments, bear the responsibility of mitigating the challenges inherent in the context of digital learning, thereby advocating for the implementation of comprehensive strategies that adhere to best practices and embrace inclusivity. By operationalizing these strategies, HEIs will be ensuring equitable opportunities and success for all students, while also preventing analogous challenges that may arise in instances of future crises limiting physical mobility.